MODELS FOR WAGES’ FORMATION IN THE REPUBLIC OF KAZAKHSTAN - N. K. Yemelina; M. A. Assanova; N. G. Kozlova (Экономика: стратегия и практика, 2018)
The purpose of the article is to conduct a selective review of the principles of empirical analysis, which helps to identify factors affecting the level of wages; to assess the differences in wages, taking into account the gender aspect and territorial position. Methodology - correlation-regression analysis for building models of wage formation using fictitious variables as factor attributes. Novelty - an analysis of factors affecting wages not only at the national level but also at the regional and sectorial levels, with an assessment of the impact of education and professional experience. Results - it is determined that the rate of return on education in Kazakhstan is 8.9%. However, this indicator is not the same for individuals of male and female sex, and varies with respect to the branches of the economy and the regions of residence. Conclusions - the proposed models allow obtaining an overall picture of the factors of salary formation in the Republic of Kazakhstan, and describing the trend characteristic for the domestic labor market.